European identity, the effect of Europeanization on nation-state identities and the Turkish dimension - Öztürk, Hande (My University, 2005)
Avrupa bazı dönemler dışında tarih boyunca hem siyasal hem de ekonomik bütünleşme isteği içinde olmuştur. Bütünleşme sürecinin üçüncü boyutu, kültürel entegrasyon ise arka planda kalmıştır. Avrupa kimliği olarak oluşturulmaya çalışılan biz duygusu ve ortak bir kimlik Avrupa Birliği’nin devamı için büyük önem taşır. Avrupa kimliği hem ortak geçmişe ve ortak özelliklere odaklanan kültürel bir kimlik hem de Avrupa Birliği’ni ve üye ülkelerin siyasal ve ekonomik ortaklıklarını sembolize eden politik bir kimliktir. Avrupa kimliği ve kültürel birlik üye ülkelerin ulus devlet kimliklerini de etkilemiştir. Birliğin lokomotifi Fransa’da Fransız kimliğinin avrupalılaşma süreci büyük değişimler geçirmiştir. Güçlü Fransız ulus devlet kimliğinden doğan “Fransız Avrupa” kavramı “Avrupalı Fransa”ya dönüşmüştür. “Tuhaf ortak” olarak anılan İngiliz kimliği özellikle Blair hükümeti döneminde Birliğe yaklaşmıştır; fakat bütün bu değişiklere rağmen Avrupa kimliği merkezde yer almaz. Türkiye de Avrupa üyelik sürecinden etkilenmiştir. Türk hukuku ve demokrasisi Avrupa ile müzakerelere başlamak için büyük değişim yaşamış, Türk ekonomisi ve sonuç olarak Türk insanının yaşam standardı artmıştır. Türkiye’nin ve Türk kimliğinin Avrupalılaşma süreci her alanda Türkiye için faydalı olmuş ve gelecekte de faydalı olacaktır.

Europe has had the wish of a complete integration both economically and politically throughout the history except some periods. The third dimension of the integration process has been at the background: cultural integration. Having a we-feeling and a common identity which are tried to be constructed as the “European Identity” are of great significance for the ongoing of the European Union. European Identity is both a cultural identity which focuses on the common past and traits of Europe and a political identity representing the European Union and the political and economic partnership the member states have. European identity and cultural unity has affected nation-state identities of the member states. In the case of France as the locomotive of the Union, Europeanization of French identity has experienced great changes. “French Europe” resulting from strong French nation-state identity has altered to “European French”. The British identity as the “awkward partner” has approached the Union in the last years especially with the Blair government. However, despite all these changes European identity, remains as a peripheral identity rather than being in the center. Turkey has also been influenced by the European accession process. Turkish law and democracy have undergone great changes to start the negotiations with the European Union. Also Turkish economy and as a result the life standards of Turkish people have increased. The Europeanization process of Turkey and Turkish identity has been and is going to be beneficial for Turkey in all respects.
Keywords: Avrupa Birliği; Kültürler arasındaki temaslar; Toplumsal değişim